The evaluation of land suitability to Upland rice (Oryza sativa L.) and Onion (Allium ascalonicum L.) in Kualuh Hulu Subdistrict Of North Labuhanbatu District - Khairi Rizki Siregar; Zulkifli Nasution; Bintang Sitorus (Universitas Sumatera Utara, 2019)
The objective of this research is to evaluate the land suitability Upland rice (Oryza sativa L.) and Onion (Allium ascalonicum L.) in Kualuh Hulu Subdistrict of North Labuhanbatu District. The methode of this research is the survay method. From the results of the overlay from the map of soil types, map of topography, and map of height place, retrieved 9 units of land use map. SPL 1 has a land area of 22.273,98 hectares, SPL 2 has a land area of 12.248 hectares, SPL 3 has a land area of 8.571,24 hectares, SPL 4 has a land area of 8.015,46 hectares, SPL 5 has a land area of 4.736,61 hectares, SPL 6 has a land area of 3.154,86 hectares, SPL 7 has a land area of 2.044,73 hectares, SPL 8 has a land area of 1.445,39 hectares and SPL 9 has a land area of 946,28 hectare. The conclusion of this research showed the highest potential of land suitability classes in set of land 1 is upland rice ( S3 rc ) and onion ( S3 wa, rc ),in set of land 2 is upland rice ( N rc ) and onion ( N rc ), in set of land 3 is upland rice ( S1 ) and onion ( S3 wa ), in set of land 4 is upland rice ( N rc ) andonion ( N rc ), in set of land 5 is upland rice ( S3 rc ) and onion ( S3 wa rc ), in set of land 6 is upland rice ( S1) and onion ( S3 wa ), in set of land 7 is upland rice ( S3 rc ) and onio ( S3 wa rc ), in set of land 8 is upland rice ( S3 rc ) and onion ( S3 wa rc ) and in set of land 9 is upland rice ( S3 rc ) and onion ( S3 wa rc ). Keywords : Land suitability, Onion, Upland rice